PEMANFAATAN BAKTERI PSEUDOMONAS FLUORESCENS, JAMUR TRICHODERMA HARZIANUM DAN SERESAH DAUN JATI (TECTONA GRANDIS) UNTUK PERTUMBUHAN TANAMAN KEDELAI PADA MEDIA TANAM TANAH KAPUR - Rohmah, Fuyudur; Rahayu, Yuni Sri; Yuliani, Yuliani (LenteraBio: Berkala Ilmiah Biologi, 2013)
The need of area for agricultural activities and plant cultivation increase so required the using of area that has not been used effectively by farmers, such as the calcareous soil as a marginal land. This research aimed to know the effect of Pseudomonas fluorescens with various concentrations were added Trichoderma harzianum and teak leaves compost on the growth and P content of soybean plants on calcareous soil. This research method used one way analysis of variance (ANOVA), that was the P. fluorescens concentrations (0, 102, 105, 109 cfu/ml) with 6 replications. The growth parameter which measured include height, biomass, amount of leaf soybean plants. Data from growth of soybean plants was analyzed by ANOVA continued least significant difference test, then P content was analyzed by descriptively. The research result showed that P. fluorescens with various concentrations, which were added by T. harzianum and teak leaves compost, affected on the growth of soybean plants (height, biomass and amount of leaf). The concentration of 109 cfu/ml of P. fluorescens affected on the optimum growth of soybean plants. In addition, the optimum concentration of P. fluorescens on the P content of soybean plants was at 105 cfu/ml.